Necessity of Surgical Site Closed Suction Drain for Pterional Craniotomy - Choi, Su Yong (J Cerebrovasc Endovasc Neurosurg, 2015)
OBJECTIVE: The aim of this study was to assess the benefit of using a prophylactic surgical site closed suction drain in pterional craniotomy. MATERIALS AND METHODS: A retrospective review was conducted on 607 consecutive patients who underwent a pterional craniotomy for treatment of intracranial anterior circulation aneurysms over a 5-year period. Between January 2000 and December 2004, 607 patients were divided into two groups, those who had a prophylactic suction drain during closure of the surgical site (drain group, DG) and those who did not (non-drain group, NDG). Head computed tomography (CT) was taken routinely on postoperative day (POD) 1, 7, and 14. Patients' demographics, incidence of surgical site complications, and courses of surgical site healing which were evaluated radiologically by the thickness of the surgical site myocutaneous layer, were analyzed between DG and NDG. RESULTS: Patients' demographics and characteristics did not differ significantly between the two groups. The head CT showed that the degree of changes in the postoperative surgical site thickness was 148% at POD 1, 209% at POD 7, and 198% at POD 14 in DG, and 118% at POD 1, 152% at POD 7, and 158% at POD 14 in NDG compared to the preoperative value. Postoperative surgical site hematoma was 7.9% (22/274) in DG and 2.4% (8/333) in NDG. CONCLUSION: Prophylactic use of an epidural and/or subgaleal closed suction drain does not appear to be necessary for prevention of postoperative surgical site hematoma as well as for promotion of surgical site healing in pterional craniotomy.